Human Resource Management of Japanese Companies in Hungary: How do Japanese and Hungarian Styles Blend?. Issue 3 (2nd July 2016) - Grill, Tunde Veronika; Maharjan, Mohan Pyari; Sekiguchi, Tomoki
ABSTRACT: A qualitative interview-based research with 32 participating companies, this article investigates the human resource management practices of Japanese subsidiaries in Hungary. The findings indicate that human resource management practices in Hungarian subsidiaries of Japanese companies are characterized as a hybrid of Japanese and Hungarian styles. Greater Japanese influence was found in the characteristics of the human resources department, corporate culture, safety practices, and trainings, whereas greater Hungarian influence was found in pay, benefits, and recruitment methods. The findings contribute uniquely to the understanding of whether and how the country-of-origin effect, localization effect, and dominance effect interplay in configuring human resource management practices in foreign subsidiaries of multinational companies.